Pemanfaatan Limbah Tutup Botol Air Mineral Sebagai Filler Pada Lapis Perkerasan Base a - Aswantu Fajri; Sazuatmo Sazuatmo (MAJALAH TEKNIK SIMES, 2021)
One of the most common plastic wastes found around us is the cap of mineral water bottles. The waste of mineral water bottle caps as a filler on the basis is expected to reduce the impact of plastic waste it self and reduce rock waste in the quarry. Tests carried out by adding fillers of mineral water bottle cap waste as much as 0%, 10%, 20%, and 30%. The ability of mineral water bottle cap waste as a filler can be tested by looking at the value of the California Bearing Ratio (CBR) generated after addition. CBR testing is carried out by the laboratory CBR test method using a CBR penetration tool. From the examiners, the results show that; base A aggregate without the addition of mineral water bottle cap waste with a CBR value of 93.38%; the addition of 10% of mineral water bottle cap waste resulted in a CBR value of 98.73%. The addition of 20% obtained a CBR value of 96.55%; and an addition of 30% resulted in a CBR value of 87.65%. The addition of 10% and 20% of mineral water bottle cap waste filler can increase the CBR base A value, because it produces a larger CBR value without addition. Meanwhile, an increase of 30% will actually reduce the strength of the base itself because the resulting CBR value is smaller. The addition of filler of mineral water bottle cap waste can increase the CBR value of base A with the right composition. Utilization of mineral water bottle cap waste at base A will reduce the amount of plastic waste and reduce environmental pollution, as well as reduce the overexploitation of rocks for base A raw material.